-(3x-5)-(5x-6)+8=-5(x-1)-(7x+5)+3

Simple and best practice solution for -(3x-5)-(5x-6)+8=-5(x-1)-(7x+5)+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(3x-5)-(5x-6)+8=-5(x-1)-(7x+5)+3 equation:



-(3x-5)-(5x-6)+8=-5(x-1)-(7x+5)+3
We move all terms to the left:
-(3x-5)-(5x-6)+8-(-5(x-1)-(7x+5)+3)=0
We get rid of parentheses
-3x-5x-(-5(x-1)-(7x+5)+3)+5+6+8=0
We calculate terms in parentheses: -(-5(x-1)-(7x+5)+3), so:
-5(x-1)-(7x+5)+3
We multiply parentheses
-5x-(7x+5)+5+3
We get rid of parentheses
-5x-7x-5+5+3
We add all the numbers together, and all the variables
-12x+3
Back to the equation:
-(-12x+3)
We add all the numbers together, and all the variables
-8x-(-12x+3)+19=0
We get rid of parentheses
-8x+12x-3+19=0
We add all the numbers together, and all the variables
4x+16=0
We move all terms containing x to the left, all other terms to the right
4x=-16
x=-16/4
x=-4

See similar equations:

| 6x-15x=x-20 | | 3k=2.4 | | 6x-15x=x—20 | | 7m/5=3 | | (15b-2)-7(2b+4)=-4 | | M-34/6-7m-21/5=1 | | x=3E-08(4532951+0.0019 | | |x+1|+|x-1|=2x | | 4(x+7=3(x-8)+x | | -17-4x=-5-5(1×5x) | | x-71=89 | | 5(x+3)+8=5x+8 | | 3^(3x-3)=36 | | n(n-3)=20 | | -2(6y-7)-y=-2(y-3) | | -4(4y-8)-y=-2(y-5) | | 9x-3x+6=x-4+10 | | m+8=34 | | 5/2a-12=1/3a+1 | | 3p+p=120 | | 7(t-5)+5t=6(2t+3)-10 | | 6+2n-1=9n+17-3n | | 4(2x+6)=4x+8 | | -7(v+4)+4v+7=7v+12 | | -0.25(x-8)+0.50(x+2)=x-3 | | 3((x+2)/2)-2((x+3)/5)+x-1=13x/10+1 | | 8x=10/5 | | 5/3=1/3+d | | 5(p-4)=7p | | -2+3k=25 | | 14j-8j-3=3 | | −1/9(x−27)+1/3(x+3)=x+4 |

Equations solver categories